Electron trapping at SiO2/4H-SiC interface probed by transient capacitance measurements and atomic resolution chemical analysis. (18th July 2018) - Fiorenza, Patrick; Iucolano, Ferdinando; Nicotra, Giuseppe; Bongiorno, Corrado; Deretzis, Ioannis; La Magna, Antonino; Giannazzo, Filippo; Saggio, Mario; Spinella, Corrado; Roccaforte, Fabrizio
Abstract: Studying the electrical and structural properties of the interface of the gate oxide (SiO2 ) with silicon carbide (4H-SiC) is a fundamental topic, with important implications for understanding and optimising the performances of metal-oxide-semiconductor field effect transistor (MOSFETs). In this paper, near interface oxide traps (NIOTs) in lateral 4H-SiC MOSFETs were investigated combining transient gate capacitance measurements ( C–t ) and state of the art scanning transmission electron microscopy in electron energy loss spectroscopy (STEM-EELS) with sub-nm resolution. The C–t measurements as a function of temperature indicated that the effective NIOTs discharge time is temperature independent and electrons from NIOTs are emitted toward the semiconductor via-tunnelling. The NIOTs discharge time was modelled also taking into account the interface state density in a tunnelling relaxation model and it allowed us to locate traps within a tunnelling distance of up to 1.3 nm from the SiO2 /4H-SiC interface. On the other hand, sub-nm resolution STEM-EELS revealed the presence of a non-abrupt (NA) SiO2 /4H-SiC interface. The NA interface shows the re-arrangement of the carbon atoms in a sub-stoichiometric SiO x matrix. A mixed sp 2 /sp 3 carbon hybridization in the NA interface region suggests that the interfacial carbon atoms have lost their tetrahedral SiC coordination.